In vitro permeation of platinum and rhodium through Caucasian skin - Franken, A.; Eloff, F.C.; Du Plessis, J.; Badenhorst, C.J.; Jordaan, A.; Du Plessis, J.L. (Toxicology in vitro, 2014)
•Platinum and rhodium are able to permeate through intact Caucasian skin.•Platinum permeation through the skin is significantly higher than rhodium permeation.•High concentrations of both metals are retained inside the skin after 24h exposure.•Dermal exposure to these metal salts could contribute to sensitisation of workers.•Good personal hygiene after a work shift is imperative to prevent ‘take-home’ effect. During platinum group metals (PGMs) refining the possibility exists for dermal exposure to PGM salts. The dermal route has been questioned as an alternative route of exposure that could contribute to employee sensitisation, even though literature has been focused on respiratory exposure. This study aimed to investigate the in vitro permeation of platinum and rhodium through intact Caucasian skin. A donor solution of 0.3mg/ml of metal, K2PtCl4 and RhCl3 respectively, was applied to the vertical Franz diffusion cells with full thickness abdominal skin. The receptor solution was removed at various intervals during the 24h experiment, and analysed with high resolution ICP-MS. Skin was digested and analysed by ICP-OES. Results indicated cumulative permeation with prolonged exposure, with a significantly higher mass of platinum permeating after 24h when compared to rhodium. The mass of platinum retained inside the skin and the flux of platinum across the skin was significantly higher than that of rhodium. Permeated and skin retained platinum and rhodium may therefore contribute to sensitisation and indicates a health risk associated with dermal exposure in the workplace.